2007
DOI: 10.1038/sj.hdy.6800950
|View full text |Cite
|
Sign up to set email alerts
|

Variation in genomic recombination rates among animal taxa and the case of social insects

Abstract: Meiotic recombination is almost universal among sexually reproducing organisms. Because the process leads to the destruction of successful parental allele combinations and the creation of novel, untested genotypes for offspring, the evolutionary forces responsible for the origin and maintenance of this counter-intuitive process are still enigmatic. Here, we have used newly available genetic data to compare genome-wide recombination rates in a report on recombination rates among different taxa. In particular, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
187
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 43 publications
14
187
1
1
Order By: Relevance
“…Wilfert et al (5) suggested that the evolution of eusociality may select for high rates of recombination, which increase genotypic diversity in workers leading to increased colony fitness. Our study also suggests that higher recombination rates increase the evolutionary rate of genes associated with worker behavior, which may facilitate the evolution of worker specialization and elaboration after caste formation.…”
Section: Discussionmentioning
confidence: 99%
“…Wilfert et al (5) suggested that the evolution of eusociality may select for high rates of recombination, which increase genotypic diversity in workers leading to increased colony fitness. Our study also suggests that higher recombination rates increase the evolutionary rate of genes associated with worker behavior, which may facilitate the evolution of worker specialization and elaboration after caste formation.…”
Section: Discussionmentioning
confidence: 99%
“…First, differential action of selection, or selection in changing environments, could give rise to differences between species (Chinnici, 1971;Charlesworth and Charlesworth, 1985;True et al, 1996). For example, artificial selection may have increased recombination rates in the domesticated species of chicken, honeybee and many plants (Rees and Dale, 1974;Burt and Bell, 1987;Otto and Barton, 2001;Ross-Ibarra, 2004;Wilfert et al, 2007;Groenen et al, 2009) in comparison with their wild progenitors.…”
Section: How Does the Methodology By Which Recombination Is Measured mentioning
confidence: 99%
“…Control of recombination rate appears to be multifaceted, with molecular, environmental and demographic factors all having a role (for example, see Wilfert et al, 2007; see also section 'Why would we see conservation of recombination rates between some species and not others?' below).…”
Section: Determinants and Correlatesmentioning
confidence: 99%
“…Genetic linkage maps are now available for many insect species (Wilfert et al, 2007;Hunter and Kole, 2008). However, high-density maps are still restricted to species whose genomes have been sequenced: fruit flies of the genus Drosophila (Chen et al, 2009), the yellow fever mosquito Aedes aegypti (Fulton et al, 2001), the red flour beetle Tribolium castaneum (Lorenzen et al, 2005), the silkworm Bombyx mori (Yamamoto et al, 2006), and the honey bee Apis mellifera (Solignac et al, 2007).…”
Section: Introductionmentioning
confidence: 99%